Natural-Derived Molecules as a Potential Adjuvant in Chemotherapy: Normal Cell Protectors and Cancer Cell Sensitizers - Hossain, Rajib; Jain, Divya; Khan, Rasel A.; Islam, Muhammad T.; Mubarak, Mohammad S.; Mohammad Saikat, Abu S. (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Cancer is a global threat to humans and a leading cause of death worldwide. Cancer treatment includes, among other things, the use of chemotherapeutic agents, compounds that are vital for treating and preventing cancer. However, chemotherapeutic agents produce oxidative stress along with other side effects that would affect the human body. Objective: The aim of the study was to reduce the oxidative stress of chemotherapeutic agents in cancer and normal cells by naturally derived compounds with anti-cancer properties, and protect normal cells from the oxidation process. Therefore, the need to develop more potent chemotherapeutics with fewer side effects has become increasingly important. Methods: Recent literature dealing with the antioxidant and anticancer activities of the naturally derived compounds, morin, myricetin, malvidin, naringin, eriodictyol, isovitexin, daidzein, naringenin, chrysin, and fisetin, has been surveyed and examined in this review. For this, data were gathered from different search engines, including Google Scholar, ScienceDirect, PubMed, Scopus, Web of Science, Scopus, and Scifinder, among others. Additionally, several patent offices such as WIPO, CIPO, and USPTO were consulted to obtain published articles related to these compounds. Result: Numerous plants contain flavonoids and polyphenolic compounds, such as morin, myricetin, malvidin, naringin, eriodictyol, isovitexin, daidzein, naringenin, chrysin, and fisetin, which exhibit antioxidant, anti-inflammatory, and anti-carcinogenic actions via several mechanisms. These compounds act as sensitizers of cancer cells and protector of healthy cells. Moreover, these compounds can reduce oxidative stress, which is accelerated by chemotherapeutics, and exhibit a potent anticancer effect on cancer cells. Conclusion: Based on these findings, more research is recommended to explore and evaluate such flavonoids and polyphenolic compounds.
Keywords: flavonoids